Perceived Effectiveness Of Veterinary Services Among Livestock Farmers In Kwara State, Nigeria - Ajoke Oluwatoyin Kayode (Universitas Serambi Mekkah, 2021)
Diseases persist to be one of the major pressures hampering the development of livestock production in Nigeria. This study examined the effectiveness of veterinary services among livestock farmers in Kwara State, Nigeria. The specific objectives were to describe the socio-economic characteristics of livestock farmers; assess farmers’ satisfaction of veterinary services; assess farmers’ perceived benefits from veterinary services and identify the constraints to veterinary services. A random sampling technique was used to select 120 respondents on whom structured questionnaire was administered. Data collected was analyzed using descriptive statistics and the Multiple Regression Analysis. Result reveals that the farmers mean age, farming experience and years of using veterinary services were 47.64 years, 18.12years and 14.63 years respectively. Farmers’ overall perception of the effectiveness of veterinary services was high (MS=2.19) and they perceived that the veterinary service providers were most effective in diagnosis of diseases (MS=2.43) and vaccination (MS=2.32). Farmers indicated that the benefit they enjoyed most was better performance of their livestock (MS=2.83) and the major constraint faced was the untimely availability (MS=2.17) and shortage (MS=2.15) of veterinary service providers. At p0.05, years of schooling (β =0.209), number of animals owned (β=0.174) and type of veterinary service provider (β=-0.186) were the determinants of farmers perception of the effectiveness of veterinary service. The study concluded that that livestock farmers had a high perception of the effectiveness of veterinary services in Kwara State, Nigeria and their perception of the effectiveness was influenced by some socio-economic characteristics. It recommends that government should establish more veterinary hospital and clinics, recruit qualified and certified veterinarian to make veterinary service accessible and affordable